1991
DOI: 10.1172/jci115020
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor (PAF) stimulates the production of PAF acetylhydrolase by the human hepatoma cell line, HepG2.

Abstract: The human hepatoma cell line, HepG2, secreted an activity that degrades platelet-activating factor (PAF) by the hydrolysis ofthe sn-2 acetyl group. This activity was Ca"+ independent, inhibited by diisopropylfluorophosphate but not by p-bromophenacyl bromide, and resistant to treatment with trypsin or pronase. Separation of HepG2-conditioned medium by gel filtration disclosed that the activity was associated with lipoproteins. An antiserum against PAF acetylhydrolase immunoprecipitated this activity. It was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
6

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 39 publications
2
31
0
6
Order By: Relevance
“…In addition, PAF stimulated the secretion of PAF acetylhydrolase in the human hepatoma cell line, Hep G2, in a cycloheximide-sensitive fashion (24). Liver PAF levels are elevated significantly 3 h after LPS exposure in this endotoxin exposure model.…”
Section: Suppression Of Lps-induced Paf Acetylhydrolase Expression Bymentioning
confidence: 65%
“…In addition, PAF stimulated the secretion of PAF acetylhydrolase in the human hepatoma cell line, Hep G2, in a cycloheximide-sensitive fashion (24). Liver PAF levels are elevated significantly 3 h after LPS exposure in this endotoxin exposure model.…”
Section: Suppression Of Lps-induced Paf Acetylhydrolase Expression Bymentioning
confidence: 65%
“…Independent studies have shown that PAF, which bears structural resemblance to fragmented, short-chain phospholipids, upregulates expression of Lp-PLA 2 mRNA in monocyte/macrophages ( 48 ) and HepG2 cells ( 53 ). Consistently, a recent study reported elevated plasma levels of both PAF and Lp-PLA 2 mass in a cohort of coronary heart disease (CHD) patients compared with a control group ( 54 ).…”
Section: Biochemical and Structural Propertiesmentioning
confidence: 76%
“…Several studies have determined that the level of PAF accumulation is determined by the PAF-AH activity (Touqui et al, 1985;Suzuki et al, 1988;Elstad et al, 1989). In addition, the magnitude of the inflammatory response to PAF may function in an autoregulatory manner because increased production of PAF stimulates the expression of PAF-AH (Satoh et al, 1991). Thus, it follows that inhibition of PAF-AH would propagate the PAF-mediated inflammatory response.…”
Section: Discussionmentioning
confidence: 99%